A Low-Profile Broadband Metasurface Antenna With Polarization Conversion Based on Characteristic Mode Analysis - Dong, Jian; Wu, Rigeng; Pan, Yaxi (Frontiers in Physics, 2022)
In this paper, a low-profile, broadband metasurface antenna for polarization conversion is proposed based on characteristic mode analysis (CMA). A new type of metasurface unit with a partially chamfered symmetrical triangular structure is designed. The inherent physical characteristics of the antenna are analyzed based on CMA, and the expected characteristic modes are selected for excitation at a suitable position. Slot-coupled feeding via microstrip line realizes the performance of wide impedance bandwidth and axial ratio bandwidth (ARBW). The measured -10 dB impedance bandwidth of 36.3% (4.38-6.32 GHz) and the 3 dB ARBW of 20.1% (5.41-6.62 GHz) are achieved. The left-hand circular polarization (LHCP) is realized, and the measured highest gain in the working frequency band is 6.05 dBic. The overall size of the designed and fabricated metasurface antenna is 0.58λ_0×0.58λ_0×0.07λ_0 at 5 GHz. The proposed metasurface antenna can be well used in C-band satellite communications due to its low profile, broadband, and circular polarization.